Cross-sectional study on differences in pain perception and behavioral distress during venipuncture between Italian and Chinese children - Sofia Bisogni; Marta Calzolai; Nicole Olivini; Daniele Ciofi; Nicola Mazzoni; Simona Caprilli; José Rafael Gonzalez Lopez; Filippo Festini (MDPI AG, 2014)
Venipuncture is perhaps the scariest aspect of hospitalization for children as it causes pain and high levels of behavioral distress. Pain is a complex experience which is also influenced by social factors such as cultural attitudes, beliefs and traditions. Studies focusing on ethnic/cultural differences in pain perception and behavioral distress show controversial results, in particular with regards to children. The aim of this paper is to evaluate differences in pain perception and behavioral manifestations between Italian and Chinese children undergoing a venipuncture, through a cross-sectional study. Behavioral distress and self-reported pain were measured in Chinese and Italian outpatient children during a standardized blood-drawing procedure, using the Observational Scale of Behavioral Distress (OSBD) and pain scales. We observed 332 children: 93 Chinese and 239 Italian. Chinese children scored higher than Italians on pain scales − mean scores 5.3 (95%CI 4.78-5.81) vs. 3.2 (95%CI 2.86-3.53) − but lower mean OSBD scores − mean 4.1 (95%CI 3.04-5.15) vs. 8.1 (95%CI 7.06-9.14). Our data suggest that Chinese children experience higher levels of pain than their Italian peers, although they show more self-control in their behavioral reaction to pain when experiencing venipuncture.